Botox, sunshine, travelling. The linguistic picture of happiness in German birthday wishes for 65-year-olds - Miller, Dorota (Papers in Linguistics, 2021)
The article aims to analyse birthday wishes as examples of linguistic politeness. The research material consists of 100 wishes for the 65th birthday, that is the moment of retiring, which appear on the most popular German websites with wishes. The main purpose of the undertaken analysis is to reconstruct the linguistic picture of happiness created in German online wishes. Highly conventionalized texts of wishes point to a system of values shared both by the sender and by the recipient of wishes (generally understood happiness/prosperity, and/or more specific values such as joy, health, material well-being, long life, future experiences, success/career, peace/rest, happy/successful relationships with loved ones, joyful birthday celebrations). These values are embedded in language and are believed to embody happiness. The article also contains comments on the structure and degree of conventionalization of birthday wishes. In addition to the traditional realisation of the act of wishing, numerous examples of breaking the genre convention are presented (including co-occurring speech acts such as thanking, praise/compliment, congratulations, toast), illustrating changes in the contemporary model of politeness.